3-D Numerical Model For Wave-Induced Seabed Response Around An Offshore Pipeline - Zuodong Liang; Jeng, Dong-Sheng (Zenodo, 2018)
Seabed instability around an offshore pipeline is one of key factors that need to be considered in the design of offshore infrastructures. Unlike previous investigations, a three-dimensional numerical model for the wave-induced soil response around an offshore pipeline is proposed in this paper. The numerical model was first validated with 2-D experimental data available in the literature. Then, a parametric study will be carried out to examine the effects of wave, seabed characteristics and confirmation of pipeline. Numerical examples demonstrate significant influence of wave obliquity on the wave-induced pore pressures and the resultant seabed liquefaction around the pipeline, which cannot be observed in 2-D numerical simulation. : {"references": ["A. C. Palmer and R. A. King, Subsea pipeline engineering. PennWell\nBooks, 2004.", "B. M. Sumer, F. H. Dixen, and J. Freds\u00f8e, \"Cover stones on liquefiable\nsoil bed under waves,\" Coastal Engineering, vol. 57, no. 9, pp. 864\u2013873,\n2010.", "J. Freds\u00f8e, \"Pipeline\u2013seabed interaction,\" Journal of Waterway, Port,\nCoastal, and Ocean Engineering, vol. 142, no. 6, p. 03116002, 2016.", "B. M. Sumer, Liquefaction around marine structures. World Scientific,\n2014.", "K. Zen and H. Yamazaki, \"Field observation and analysis of\nwave-induced liquefaction in seabed,\" Soils and Foundations, vol. 31,\nno. 4, pp. 161\u2013179, 1991.", "H. B. Seed and M. S. Rahman, \"Wave-induced pore pressure in relation\nto ocean floor stability of cohesionless soils,\" Marine Geotechnology,\nvol. 3, no. 2, pp. 123\u2013150, 1978.", "T. Yamamoto, \"Wave-induced pore pressures and effective stresses in\ninhomogeneous seabed foundations,\" Ocean Engineering, vol. 8, pp.\n1\u201316, 1981.", "O. S. Madsen, \"Wave-induced pore pressures and effective stresses in a\nporous bed,\" G\u00b4eotechnique, vol. 28, no. 4, pp. 377\u2013393, 1978.", "B. M. Sumer, J. Freds\u00f8e, S. Christensen, and M. L. Lind,\n\"Sinking/floatation of pipelines and other objects in liquefied soil under\nwaves,\" Coastal Engineering, vol. 38, pp. 53\u201390, 1999.\n[10] B. M. Sumer, C. Truelsen, T. Sichmann, and J. Freds\u00f8e, \"Onset of scour\nbelow pipelines and self-burial,\" Coastal engineering, vol. 42, no. 4, pp.\n313\u2013335, 2001.\n[11] T. C. Teh, A. C. Palmer, and J. S. Damgaard, \"Experimental study of\nmarine pipelines on unstable and liquefied seabed,\" Coastal Engineering,\nvol. 50, pp. 1\u201317, 2003.\n[12] C. Zhou, G. Li, P. Dong, J. Shi, and J. Xu, \"An experimental study\nof seabed responses around a marine pipeline under wave and current\nconditions,\" Ocean Engineering, vol. 38, no. 1, pp. 226\u2013234, 2011.\n[13] D. Jeng and Y. Lin, \"Wave\u2013induced pore pressure around a buried\npipeline in gibson soil: finite element analysis,\" International Journal\nfor Numerical and Analytical Methods in Geomechanics, vol. 23, no. 13,\npp. 1559\u20131578, 1999.\n[14] D.-S. Jeng and L. Cheng, \"Wave-induced seabed instability around a\nburied pipeline in a poro-elastic seabed,\" Ocean Engineering, vol. 27,\nno. 2, pp. 127\u2013146, 2000. [15] A. H. D. Cheng and P. L.-F. Liu, \"Seepage force on a pipeline buried\nin a poroelastic seabed under wave loading,\" Applied Ocean Research,\nvol. 8, no. 1, pp. 22\u201332, 1986.\n[16] F. Gao, D. S. Jeng, and H. Sekiguchi, \"Numerical study on\nthe interaction between non-linear wave, buried pipeline and\nnon-homogenous porous seabed,\" Computers and Geotechnics, vol. 30,\nno. 6, pp. 535\u2013547, 2003.\n[17] F.-P. Gao and Y.-X. Wu, \"Non-linear wave induced transient response\nof soil around a trenched pipeline,\" Ocean Engineering, vol. 33, pp.\n311\u2013330, 2006.\n[18] X.-L. Zhou, D.-S. Jeng, Y.-G. Yan, and J.-H. Wang, \"Wave-induced\nmulti-layered seabed response around a buried pipeline,\" Ocean\nEngineering, vol. 72, pp. 195\u2013208, 2013.\n[19] Z. Lin, Y. Guo, D.-s. Jeng, C. Liao, and N. Rey, \"An integrated numerical\nmodel for wave\u2013soil\u2013pipeline interactions,\" Coastal Engineering, vol.\n108, pp. 25\u201335, 2016.\n[20] H.-Y. Zhao, D.-S. Jeng, Z. Guo, and J.-S. Zhang, \"Two dimensional\nmodel for pore pressure accumulations in the vicinity of a buried\npipeline.\" Journal of Offshore Mechanics and Arctic Engineering, ASME,\nvol. 136(4), p. 042001, 2014.\n[21] P. Higuera, J. Lara, and I. Losada, \"Realistic wave generation and active\nwave absorption for vavier-stokes models: Application to openfoam,\"\nCoastal Engineeirng, vol. 71, pp. 102\u2013118, 2013.\n[22] F. Engelund, On the laminar and turbulent flows of ground water through\nhomogeneous sand. Akad. for de Tekniske Videnskaber, 1953.\n[23] H. Burcharth and O. Andersen, \"On the one-dimensional steady and\nunsteady porous flow equations,\" Coastal engineering, vol. 24, no. 3-4,\npp. 233\u2013257, 1995.\n[24] M. A. Biot, \"General theory of three-dimensional consolidation,\"\nJournal of Applied Physics, vol. 26, no. 2, pp. 155\u2013164, 1941.\n[25] J. Ye and D.-S. Jeng, \"Response of seabed to natural loading-waves and\ncurrents,\" Journal of Engineering Mechanics, ASCE, vol. 138, no. 6, pp.\n601\u2013613, 2012.\n[26] J. R. C. Hsu and D.-S. Jeng, \"Wave-induced soil response in an\nunsaturated anisotropic seabed of finite thickness,\" International Journal\nfor Numerical and Analytical Methods in Geomechanics, vol. 18, no. 11,\npp. 785\u2013807, 1994.\n[27] D. Jeng and J. Hsu, \"Wave-induced soil response in a nearly saturated\nsea-bed of finite thickness,\" Geotechnique, vol. 46, no. 3, pp. 427\u2013440,\n1996.\n[28] D.-S. Jeng, Porous Models for Wave-seabed Interactions. Springer,\n2012.\n[29] B. Liu, D.-S. Jeng, G. Ye, and B. Yang, \"Laboratory study for pore\npressures in sandy deposit under wave loading,\" Ocean Engineering,\nvol. 106, pp. 207\u2013219, 2015.\n[30] M. Umeyama, \"Coupled piv and ptv measurements of particle velocities\nand trajectories for surface waves following a stedy current,\" Journal of\nWaterway, Port, Coastal and Ocean Engineering , ASCE, vol. 137, pp.\n85\u201394, 2011.\n[31] M. Mattioli, J. M. Alsina, A. Mancinelli, M. Miozzi, and M. Brocchini,\n\"Experimental investigation of the nearbed dynamics around a\nsubmarine pipeline laying on different types of seabed: the interaction\nbetween turbulent structures and particles,\" Advances in water resources,\nvol. 48, pp. 31\u201346, 2012."]}